Analysis of Platelet Glycoprotein Ia (α2 Integrin) Allele Frequencies in Three North American Populations Reveals Genetic Association between Nucleotide 807C/T and Amino Acid 505 Glu/Lys (HPA-5) Dimorphisms - Reiner, Alexander P.; Aramaki, Kaelen M.; Teramura, Gayle; Gaur, Lakshmi (Thrombosis and Haemostasis, 1998)
Glycoprotein Ia (α2 integrin) is a subunit of the heterodimeric membrane complex (GPIa/IIa) that mediates platelet adhesion to collagen. Several nucleotide sequence variations of GPIa have been described. A nucleotide 1648 G/A dimorphism that leads to a Glu/Lys substitution at amino acid 505 is responsible for the human platelet antigen system, HPA-5. Recently, two other linked GPIa nucleotide dimorphisms involving codons Phe224 and Thr246 were identified: a C/T substitution at nucleotide 807 and a G/A substitution at nucleotide 873 (1). Using restriction enzyme digestion of amplified GPIa genomic DNA fragments (PCR-RFLP) to distinguish genotypes, we have determined the allele frequencies of the GPIa 807C/T and Glu/Lys505 dimorphisms in three North American populations, and a panel of non-human primates. Our results indicate a genetic relationship between the 807C/T and Glu/Lys505 dimorphisms that leads to an evolutionary model of GPIa isoforms.